2015
DOI: 10.1111/jvec.12131
|View full text |Cite
|
Sign up to set email alerts
|

New baseline environmental assessment of mosquito ecology in northern Haiti during increased urbanization

Abstract: The catastrophic 2010 earthquake in Port-au-Prince, Haiti, led to the large-scale displacement of over 2.3 million people, resulting in rapid and unplanned urbanization in northern Haiti. This study evaluated the impact of this unplanned urbanization on mosquito ecology and vector-borne diseases by assessing land use and change patterns. Land-use classification and change detection were carried out on remotely sensed images of the area for 2010 and 2013. Change detection identified areas that went from agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 60 publications
2
40
0
1
Order By: Relevance
“…Anopheles , Culex , and Haemagogus are known to transmit disease in certain geographic areas, including malaria, West Nile virus, and yellow fever (Cardoso et al., ; Centres for Disease Control and Prevention; World Health Organization). Aedes , a vector for Zika and dengue fever, was notably absent from our mesocosms despite a tendency to readily colonize a variety of man‐made habitats (Harrington, Ponlawat, Edman, Scott, & Vermeylen, ; Samson et al., ). It is thought that Aedes thrive in urban and suburban areas (Davis, Kline, & Kaufman, ; Tsuzuki, Huynh, Luu, Tsunoda, & Takagi, ), but it is unclear what threshold of urbanization promotes Aedes proliferation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Anopheles , Culex , and Haemagogus are known to transmit disease in certain geographic areas, including malaria, West Nile virus, and yellow fever (Cardoso et al., ; Centres for Disease Control and Prevention; World Health Organization). Aedes , a vector for Zika and dengue fever, was notably absent from our mesocosms despite a tendency to readily colonize a variety of man‐made habitats (Harrington, Ponlawat, Edman, Scott, & Vermeylen, ; Samson et al., ). It is thought that Aedes thrive in urban and suburban areas (Davis, Kline, & Kaufman, ; Tsuzuki, Huynh, Luu, Tsunoda, & Takagi, ), but it is unclear what threshold of urbanization promotes Aedes proliferation.…”
Section: Discussionmentioning
confidence: 94%
“…The very characteristics that make guppies good candidates for introduction, such as live birth and sperm storage, also make them successful ecosystem invaders. Deacon et al (2011) Aedes, a vector for Zika and dengue fever, was notably absent from our mesocosms despite a tendency to readily colonize a variety of manmade habitats (Harrington, Ponlawat, Edman, Scott, & Vermeylen, 2008;Samson et al, 2015). It is thought that Aedes thrive in urban and suburban areas (Davis, Kline, & Kaufman, 2016;Tsuzuki, Huynh, Luu, Tsunoda, & Takagi, 2009), but it is unclear what threshold of urbanization promotes Aedes proliferation.…”
Section: Implications For Managementmentioning
confidence: 94%
“…Furthermore, several studies conducted worldwide on land use effect demonstrated a strong affinity of Ae. albopictus for urbanized and anthropized environments [10,16,19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that urban areas, open agricultural areas, and forested areas affected Ae. albopictus presence [10,16,23,41].…”
Section: Environmental Datamentioning
confidence: 99%
See 1 more Smart Citation